A novel treatment strategy for preterm birth: Intra-vaginal progesterone-loaded fibrous patches - YAVUZ, AYŞE NUR; KABASAKAL, LEVENT; ÇAM, MUHAMMET EMİN; GÜNDÜZ, OĞUZHAN (ELSEVIER, 2020)
Progesterone-loaded poly(lactic) acid fibrous polymeric patches were produced using electrospinning and pressurized gyration for infra-vaginal application to prevent preterm birth. The patches were intravaginally inserted into rats in the final week of their pregnancy, equivalent to the third trimester of human pregnancy. Maintenance tocolysis with progesterone-loaded patches was elucidated by recording the contractile response of uterine smooth muscle to noradrenaline in pregnant rats. Both progesterone-loaded patches indicated similar results from release and thermal studies, however, patches obtained by electrospinning had smaller average diameters and more uniform dispersion compared to pressurized gyration. Patches obtained by pressurized gyration had better results in production yield and tensile strength than electrospinning; thereby pressurized gyration is better suited for scaled-up production. The patches did not affect cell attachment, viability, and proliferation on Vero cells negatively. Consequently, progesterone-loaded patches are a novel and successful treatment strategy for preventing preterm birth.
Keywords: Progesterone; Pressurized gyration; Electrospinning; Fibers; Polymeric patch; Preterm birth; IN-VITRO; PRESSURIZED GYRATION; DELIVERY; OVARIECTOMY; INHIBITION; NANOFIBERS; PREVENTION; ESTRADIOL; MEMBRANES; AIR